An update on renal scarring after urinary tract infection in children: what are the risk factors?. Issue 6 (December 2019) - Kosmeri, Chrysoula; Kalaitzidis, Rigas; Siomou, Ekaterini
Summary: Aim: The aim of this study was to present updated information on clinical, laboratory, and imaging risk factors and predictors of renal scarring after first or recurrent febrile UTIs, which may be associated with renal scarring. Methods: PubMed was searched for current data on possible risk factors and predictors of renal scarring after febrile urinary tract infections in children. Results: Recurrence of acute pyelonephritis is an independent risk factor for renal scarring, while the duration of fever before treatment initiation is mainly associated with acute pyelonephritis and its severity. Severe vesicoureteral reflux is an important independent risk factor for the development of renal scarring after a febrile urinary tract infection. Conclusions: Certain clinical parameters could be used to identify children at high risk for renal scarring after febrile urinary tract infection, helping clinicians to reserve dimercaptosuccinic acid scan for selected cases.